Microstructural evolution & corrosion behavior of Laser –powder-bed–fused Inconel 718 subjected to surface and heat treatments - O.V. Mythreyi; B.K. Nagesha; R. Jayaganthan (Journal of Materials Research and Technology, 2022)
Inconel 718 is an alloy that is rapidly rising as a potential candidate for production of geometrically complex components through laser-powder–bed–fusion (LPBF). The area of focus in this research field is centered on mechanical property evaluation, but not on corrosion behavior assessment. Hence, the objective of the present work is to understand the impact of post processing conditions on the microstructural evolution, hardness, surface topology and corrosion behavior of Inconel 718 manufactured through LPBF, followed by both mechanical and thermal post processing treatments. The printed samples are subjected to post deposition treatments such as stress relieving, solutionizing, ageing and shot peening. The secondary precipitate evolution was characterized using X-ray diffraction, optical and electron microscopy and hardness testing. Potentiodynamic polarization and Electrochemical Impedance spectroscopy tests were conducted on all the specimen conditions to determine the corrosion behavior in an acidic environment. The level of electrochemical activity and the passivation strength between the as built and post processed specimens were contrasted, and the fractographic images were analyzed for elemental distribution in the corrosion pits. This work substantiates the degradation mechanism of Inconel 718 and elucidates the role of post processing treatments in corrosion control. The optimum combination of heat treatment and shot peening procedures have been proposed for improving the surface finish, hardness and corrosion resistance of LPBFed Inconel 718 alloy.Patent pending: IP63005